A NEW SOCIETY OR A SOCIAL AND ECOLOGICAL TSUNAMI? - Boff, Leonardo (La Sociología en sus Escenarios, 2012)
Abstract. In this paper Leonardo Boff it sends the idea, that this before a systemic and terminal crisis of Capitalism, and is not a cyclical crisis. Boff maintains that the present crisis of Capitalism is than conjunctural and structural more. He is terminal. Said in other words: the conditions for their reproduction have been destroyed, is because the commodities and services that can offer have arrived at the limit by the devastation of the nature, is by the radical disorganization of the social relations, dominated by a market economy in which the financial capital predominates. The dominant tendency is to think that it is possible to be left the crisis, returning to which there was before, with small corrections, guaranteeing the growth, recovering use and assuring gains. Therefore, the businesses will continue as usual. Boff sees indications in many parts of the sprouting of a ecocentrada and biocentrada world-wide society. A world-wide joint prevails, the creation of organisms that make another way viable coexist, and a political representation ligature to the general yearnings and not to the interests of the market. It is necessary to reconstruct the social life. Resumen. En un artículo Leonardo Boff lanza la idea, de que se esta ante una crisis sistémica y terminal del capitalismo, y no es una crisis cíclica. Boff sostiene que la crisis actual del capitalismo es más que coyuntural y estructural. Es terminal.Dicho en otras palabras: las condiciones para su reproducción han sido destrozadas, sea porque los bienes y servicios que puede ofrecer han llegado al límite por la devastación de la naturaleza, sea por la desorganización radical de las relaciones sociales, dominadas por una economía de mercado en la que predomina el capital financiero. La tendencia dominante es pensar que se puede salir de la crisis, volviendo a lo que había antes, con pequeñas correcciones, garantizando el crecimiento, recuperando empleo y asegurando ganancias. Por lo tanto, los negocios continuarán como de costumbre.Boff ve indicios en muchas partes del surgimiento de una sociedad mundial ecocentrada y biocentrada. Se impone una articulación mundial, la creación de organismos que hagan viable otro modo de convivir, y una representación política ligada a los anhelos generales y no a los intereses del mercado. Hay que reconstruir la vida social.